Africa and the Digital Information Commons: An Overview - Armstrong, Chris; Ford, Heather (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2006)
Digital technologies and global electronic networks present unparalleled opportunities for international knowledge sharing and collaboration. But these same technologies and networks can also be used by authors in ways that significantly limit access and sharing for the purposes of education, innovation, and development. Through the efforts of librarians, archivists, academics and activists, vast new reserves of information and knowledge are being made available for free public consumption, and even adaptation, on the Internet. At the same time, however, electronic networks and digital technologies are being used to limit non-commercial access to some learning materials. For example, large educational publishers charge high subscription fees to universities for access to databases, with restrictions on use that are often more prohibitive than in the offline, paperbased environment. This fundamental schism present in the digital, globally-networked era – between the building of an “information commons” on the one hand, and the privatisation of knowledge on the other – is generating a variety of dynamic activist responses, including the free/libre open source software (FLOSS) movement, the “open access” movement in scholarly communication, and the “open content” approach to online sharing and collaboration among authors. The open access movement revolves mostly around the practice of academics making their research outputs and writings freely available on the Internet, either through open access online journals or online institutional repositories (archives). The open content movement is in some cases even broader than open access, encouraging online adaptation of materials by users, with the Wikipedia collaborative encyclopedia being perhaps the best-known such project. Another important open content initiative is the Creative Commons (cc) licensing system, which allows authors to adopt a “some rights reserved” approach when publishing their materials online. Under the terms of a cc licence, users are permitted unlimited copying and distribution of materials, and in some cases, are permitted to even adapt and/or derive commercial benefit from the materials. Open access and open content initiatives aim not to eliminate copyright in the online environment but rather to ensure that copyright does not restrict the potential of new technology to overcome barriers to access and innovation. The debates around the information commons and the restrictive practices of copyright rights-holders in the online environment are of particular relevance to the developing world and the African continent. Much of the world’s copyrighted material is owned by developed-world multinationals, leaving developing nations as the “payers” or consumers of knowledge and culture, and the developed world as the “payees” in much of the flow of monetary value derived from copyrighted materials. This article outlines the global information commons debates and players, and then focuses on efforts to maximise the potential benefits of digital networks for the developing world, and in particular Africa.